Mulheres da aroeira e o trabalho associado: ações organizativas de extrativistas em Piaçabuçu, Alagoas - Maciel, Kleciane Nunes (Universidade Federal de São Carlos, 2020)
The present dissertation had as general objective to identify the actions of women's organizational strategies and socioeconomic reproduction strategies of the “Associação Aroeira” in the municipality of Piaçabuçu, Alagoas, in the context of associated work. It is a study case, characterized with an exploratory and descriptive research, whose approach used is the quali-quantitative. The methodological path was based on the semi-structured interview, documentary research and direct observation. The data collected were analyzed primarily from the qualitative analysis. The results of this investigation indicate that the social organization of women extractivists was fundamental for the construction of a self-managed scio-productive system, which in turn, still has problems inherent to self-management that must be overcome to reach higher levels of cooperativism and strengthening organizational. However, associated work presents itself as a strategy for the socioeconomic reproduction of extractivist women in the “Associação Aroeira” expanding job opportunities and creation of income, mainly promoting greater social engagement, the achievement of gains in they self-esteem, financial independence and the autonomy of women. Therefore, it is concluded that associativism enabled the satisfaction of needs inherent in the living conditions of rural women so important regarding the improvement of the income level and economic conditions. The practice ecological aspects of the extraction of aroeira and the accumulation of knowledge of the activity in the region have also made it possible for these women to be immersed in an environment that generates a situation of greater sustainability. This one factor is essential for conserving local biodiversity and structuring the adopted socio-productive system.
Women from aroeira and the associated work: organizational actions of extractivim in Piaçabuçu, Alagoas
Keywords: Mulheres rurais e trabalho associado; Extrativismo da aroeira rosa; Associativismo; Rural women and associated work; Extraction of pink pepper; Associativism; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA RURAL